Adenosine A2A receptors modulate the dopamine D2 receptor‐mediated inhibition of synaptic transmission in the mouse prefrontal cortex. (2nd April 2018) - Real, Joana I.; Simões, Ana Patrícia; Cunha, Rodrigo A.; Ferreira, Samira G.; Rial, Daniel
Abstract: Prefrontal cortex (PFC) circuits are modulated by dopamine acting on D1 ‐ and D2 ‐like receptors, which are pharmacologically exploited to manage neuropsychiatric conditions. Adenosine A2A receptors (A2 A R) also control PFC‐related responses and A2 A R antagonists are potential anti‐psychotic drugs. As tight antagonistic A2 A R–D2 R and synergistic A2 A R–D1 R interactions occur in other brain regions, we now investigated the crosstalk between A2 A R and D1 /D2 R controlling synaptic transmission between layers II/III and V in mouse PFC coronal slices. Dopamine decreased synaptic transmission, a presynaptic effect based on the parallel increase in paired‐pulse responses. Dopamine inhibition was prevented by the D2 R‐like antagonist sulpiride but not by the D1 R antagonist SCH23390 and was mimicked by the D2 R agonist sumanirole, but not by the agonists of either D4 R (A‐412997) or D3 R (PD128907). Dopamine inhibition was prevented by the A2 A R antagonist, SCH58261, and attenuated in A2 A R knockout mice. Accordingly, triple‐labelling immunocytochemistry experiments revealed the co‐localization of A2 A R and D2 R immunoreactivity in glutamatergic (vGluT1‐positive) nerve terminals of the PFC. This reported positive A2 A R–D2 R interaction controlling PFC synaptic transmission provides a mechanistic justification for the anti‐psychotic potential of A2 A R antagonists. Abstract : Here, we show that the D2 R controls the glutamatergic synaptic transmission in the PFC and, by blocking or deleting the A2A R, that a synergistic interaction between A2A R and D2 R in the prefrontal cortex is prevalent. Collectively, our data offer new windows of opportunities for therapeutic interventions involving the dopaminergic and the adenosinergic systems in pathological situations related to the prefrontal cortex.